Can we differentiate malignant peripheral nerve sheath tumor from benign neurofibroma without invasive sampling - Simsek, Fikri Selcuk; Akarsu, Saadet; Narin, Yavuz (World Journal of Nuclear Medicine, 2019)
One of the most important benign tumors in neurofibromatosis type 1 (NF1) is plexiform neurofibroma, and there is a risk of developing malignant peripheral nerve sheath tumor (MPNST) throughout life approximately 10%. However lesion characterization by anatomical imaging methods are not possible. Because of that most of cases goes to biopsy. Using of fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) for lesion characterization can be helpful in NF1 patients. We aimed to present an example of the efficacy of FDG-PET/CT in distinguishing benign neurofibroma from MPNST. A 6-year-old male patient who had NF1 admitted to emergency service due to high fever. Acute upper respiratory tract infection was diagnosed; antipyretic and abundant fluid intake was suggested. When high fever continued, the patient referred to our hospital on detection of axillary lymphadenopathy. Leukocytosis was detected in patient's blood count. Sedimentation was 54 mm/h, C-reactive protein 166 g/L, and lactate dehydrogenase 276U/L. Blood and throat cultures did not show pathogenic bacteria. In serological tests, VZV-IgG, EBV-VCA-IgG, and CMV-IgG were avidite positive; Hepatitis B Ag, Anti-HIV, Anti-HAV IgG and IgM, Anti-HCV, EBV-VCA IgM, and VZV-IgM were negative. Based on these results, cervical and thoracic contrast-enhanced computed tomography was performed on preliminary diagnosis of MPNST. Solid lesions with rounded margins, large one being 49 mm in size, that extend from superior mediastinum to posterior mediastinum, left axillary region, and left part of neck were detected, and they were surrounding the vascular structures. Since neurofibroma, MPNST, and lymphoma could not be distinguished, patient referred to FDG-PET/CT scanning. In FDG-PET/CT, highest lesion maximum standardized uptake value (SUVmax) was 1.5; SUVmaxlesion/SUVmaxliver 1.0, and SUVmax/ SUV mean liver 1.5. Biopsy from mediastinal and axillary region did not have LN structure and was positive for S-100 immunostaining, and patient was diagnosed as benign neurofibroma. We believe that there is no need for biopsy in lesions considered benign based on FDG-PET/CT parameters.
Keywords: Malignant peripheral nerve sheath tumor; neurofibromatosis; positron-emission tomography/computed tomography